Utilization of Content Based Image Retrieval with Histogram. Equalization (He) for Linking Heart Disease. Using Palm Images - Permono, Diqie Shodiq (Prosiding International conference on Information Technology and Business (ICITB), 2018)
In CBIR based on images that are seen not the similarity of the image, but the similarity of the distribution of images in the compared image. In general, CBIR based on Histogram is known as Equivalent Histogram method. calculations using the Equivalent Histogram difference can set the order of the highest level of image similarity.In Indonesia, the number of experts in the field of medicine that uses palm diagnosis skills is still very little, this expertise is usually controlled by doctors of traditional and natural medicine. Therefore this writing makes it possible for Doctors in Hospitals or other Medical Centers and Clinics to be able to master it and the program by being trained in advance on how to use it. Because of that the writer took the title "Image Processing to Know the Relationship of Heart Disease with the Image of the Palm Using the Content-Based Image Retrieval (CBIR) Method". The research methodology will use Data Collection : Before Detection performed Capturing Photo Images with a minimum Camera. 5 mega pixels HP ASUS Zenfone 5 on the patient's palm , Experiments : In the experiment, there are two processes, without using the Equalization Histogram and using the Equalization Histogram enhancement. , Image Search : After the Match Image is done and compared to the reference image, the histogram will appear. which can measure the similarity of the Reference Image with a Matching Image of Value that approaches the Reference Image., Design : At this stage the image retrival system is designed using Visual Basic.Net Programming. This research is useful for the knowledge of the community and also doctors because of the existence of a traditional, simple, inexpensive disease detection system for the community.Keyword_ palm image, Histogram Equalization (HE), CBIR (Content Based Image Retrieval , Heart Disease